2013
DOI: 10.1128/mbio.00206-13
|View full text |Cite
|
Sign up to set email alerts
|

EsiB, a Novel Pathogenic Escherichia coli Secretory Immunoglobulin A-Binding Protein Impairing Neutrophil Activation

Abstract: In this study, we have characterized the functional properties of a novel Escherichia coli antigen named EsiB (E. coli secretory immunoglobulin A-binding protein), recently reported to protect mice from sepsis. Gene distribution analysis of a panel of 267 strains representative of different E. coli pathotypes revealed that esiB is preferentially associated with extraintestinal strains, while the gene is rarely found in either intestinal or nonpathogenic strains. These findings were supported by the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Recent studies [30][33], including those reported by our group [34], [35], have postulated that this microorganism has adapted to the human body by developing a sophisticated network of virulence and colonization factors. Among these adhesins, iron-uptake systems and IgA binding proteins may allow E. coli to out-compete the many species occupying an overcrowded environment such as the intestine.…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies [30][33], including those reported by our group [34], [35], have postulated that this microorganism has adapted to the human body by developing a sophisticated network of virulence and colonization factors. Among these adhesins, iron-uptake systems and IgA binding proteins may allow E. coli to out-compete the many species occupying an overcrowded environment such as the intestine.…”
Section: Discussionmentioning
confidence: 92%
“…The phagocytic role of serum IgA in other bacterial species is more controversial, like that of Neisseria spp., the causative agents of gonorrhea ( N. gonorrhoeae ) and meningitis ( N. meningitidis ) . Some studies have reported IgA‐opsonized bacteria being phagocytosed, whereas others fail to observe such a phenomenon . Under “normal” conditions (not vaccine studies) serum IgAs often fail to induce phagocytosis of Neisseria spp.…”
Section: Bacteriamentioning
confidence: 99%
“…These proteins interact with the Fc interdomain region between the Cα2 and Cα3 domains, competing for FcαRI binding, and inhibit IgA Fc functions in natural infections . An IgA‐binding protein has also been identified in pathogenic E. coli (EsiB) which impairs neutrophil activation via IgA . Vaccination and mAb therapy aiming to increase serum IgA levels may overwhelm bacterial evasion mechanisms and thus induce effective clearance of bacteria via IgA/FcαRI activation.…”
Section: Bacteriamentioning
confidence: 99%
“…In turn, pathogenic bacteria have had the opportunity to evolve complex systems to defend against attacks by the human immune system, or even to subvert them for their own gain 19 . For instance, Vibrio cholerae strains have been shown to avoid SIgA by down-regulating certain receptors in vivo 40 , while pathogenic Escherichia coli strains can express a specific SIgA binding antigen that interferes with immune signaling 41 . Resistance to AMPs has also been observed primarily though avoidance by modifying target molecules 42; 43 , while oxidative stress resistance takes the form of detoxifying enzymes such as catalase, peroxidase, and superoxide dismutase 44; 45 .…”
Section: Reducing Gut Colonization and Growth Of Harmful Bacteriamentioning
confidence: 99%